2000
DOI: 10.1016/s0304-3959(99)00283-3
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin affects glutamatergic excitatory neurotransmission in the rat dorsal horn

Abstract: We investigated the effects of gabapentin (GBP) on glutamatergic synaptic transmission in the dorsal horn of the rat spinal cord. Patch clamp whole cell recordings were made from superficial and deep dorsal horn neurons of rat spinal cord slices. In the majority of neurons in the superficial lamina, GBP decreased the amplitudes of evoked excitatory postsynaptic currents (evoked EPSCs) mediated by either non-NMDA or NMDA receptors. In contrast, neurons in the deep lamina showed variable effects, with a lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 29 publications
6
102
0
3
Order By: Relevance
“…47 On the other hand, in healthy volunteers and studies involving patients with epilepsy, GABA levels were increased after oral ingestion of gabapentin. 48,49 Furthermore, gabapentin was found to inhibit both the excitatory synaptic transmission in vitro 50 and the neuronal response to noxious electrical and mechanical stimulation in vivo mediated by a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid 51 and decrease glutamate levels in the rat brain. 52 The above human and rodent data suggest possible mechanisms underlying both the anxiolytic and sedative properties observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…47 On the other hand, in healthy volunteers and studies involving patients with epilepsy, GABA levels were increased after oral ingestion of gabapentin. 48,49 Furthermore, gabapentin was found to inhibit both the excitatory synaptic transmission in vitro 50 and the neuronal response to noxious electrical and mechanical stimulation in vivo mediated by a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid 51 and decrease glutamate levels in the rat brain. 52 The above human and rodent data suggest possible mechanisms underlying both the anxiolytic and sedative properties observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the antinociceptive mechanisms of spinal gabapentin remain unclear, several hypotheses have been suggested. It has been reported that gabapentin decreases glutamate concentrations and inhibits the release of glutamate and glutamatergic synaptic transmission presynatically (15)(16)(17). Glutamate acts on the NMDA receptor and non-NMDA receptor and shows the excitatory effect (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the drug possesses a generic analgesic and antihyperalgesic effect by modifying channels involved in nociception (86,96) and neurotransmitter release (133). Confirmation from clinical studies, have shown that gabapentin is effective against pain in cancer patients, as well (134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149).…”
Section: Gabapentinmentioning
confidence: 98%